Pengujian Sifat Mekanis Tanah Sempadan Sungai dengan Pendekatan Uji Triaxial - Fauzi, Marguan; Minaka, Utari Sriwijaya; Nurmawan, Tiara Salsabiela (Jurnal Talenta Sipil, 2025)
In construction planning, the condition of the soil must be given special attention in building a bridge which will later become the foundation, where during the rainy season it is often inundated with water/floods which can cause a wet-dry phase in the soil along the river. The aim of this research is to identify soil characteristics in the form of physical and mechanical properties of the soil on the border of Lubuk Mumpo village and determine the effect of changes in soil water content values with variations in the optimum water content mixture (Wopt), Wopt -10% Wopt, Wopt -20% Wopt and Wopt +10% Wopt, Wopt +20% Wopt to the triaxial value. The research method used is experimental in the laboratory. The research results showed that the soil conditions in Lubuk Mumpo village based on tests carried out were characterized by inorganic clay with medium-high plasticity and a uniformity coefficient (Cu) value of 16 which was well graded with a value of 16>15 and a Cc value of 0.25 and variation. The optimum water content obtained by Wopt is 29% and Wopt variations can also be determined, namely Wopt - 10% Wopt, Wopt -20% Wopt, Wopt +10% Wopt and Wopt +20% Wopt. The highest shear strength occurred when reducing Wopt -10% Wopt, namely Ø 9,980◦, an increase from Woptimum and for adding Wopt +10% Wopt, the shear strength decreased to minus, namely Ø – 5,294◦.